Hepatic de novo lipogenesis is suppressed and fat oxidation is increased by omega-3 fatty acids at the expense of glucose metabolism - Green, Charlotte J (BMJ Open Diabetes Res Care, 2020)
OBJECTIVE: Increased hepatic de novo lipogenesis (DNL) is suggested to be an underlying cause in the development of nonalcoholic fatty liver disease and/or insulin resistance. It is suggested that omega-3 fatty acids (FA) lower hepatic DNL. We investigated the effects of omega-3 FA supplementation on hepatic DNL and FA oxidation using a combination of human in vivo and in vitro studies. RESEARCH DESIGN AND METHODS: Thirty-eight healthy men were randomized to take either an omega-3 supplement (4 g/day eicosapentaenoic acid (EPA)+docosahexaenoic acid (DHA) as ethyl esters) or placebo (4 g/day olive oil) and fasting measurements were made at baseline and 8 weeks. The metabolic effects of omega-3 FAs on intrahepatocellular triacylglycerol (IHTAG) content, hepatic DNL and FA oxidation were investigated using metabolic substrates labeled with stable-isotope tracers. In vitro studies, using a human liver cell-line was undertaken to gain insight into the intrahepatocellular effects of omega-3 FAs. RESULTS: Fasting plasma TAG concentrations significantly decreased in the omega-3 group and remained unchanged in the placebo group. Eight weeks of omega-3 supplementation significantly decreased IHTAG, fasting and postprandial hepatic DNL while significantly increasing dietary FA oxidation and fasting and postprandial plasma glucose concentrations. In vitro studies supported the in vivo findings of omega-3 FAs (EPA+DHA) decreasing intracellular TAG through a shift in cellular metabolism away from FA esterification toward oxidation. CONCLUSIONS: Omega-3 supplementation had a potent effect on decreasing hepatic DNL and increasing FA oxidation and plasma glucose concentrations. Attenuation of hepatic DNL may be considered advantageous; however, consideration is required as to what the potential excess of nonlipid substrates (eg, glucose) will have on intrahepatic and extrahepatic metabolic pathways. TRIAL REGISTRATION NUMBER: NCT01936779.